Co-production of cement and carbon nanotubes with a carbon negative footprint. (March 2017) - Licht, Stuart
Highlights: Conventional and C2CNT (or CO2 to carbon nanotube) cement plants are compared. The conventionalplant emits 1.1 ton of CO2 per ton cement produced. The C2NT plant emits no CO2 & converting it to a valuable CNT co-product (CNTs). In the C2CNT plant CNTs are produced by molten carbonate electrolysis of CO2 . Abstract: C2CNT (CO2 to carbon nanotube) cement plants are introduced and analyzed with a significant economic incentive to eliminate current plant CO2 greenhouse gas emissions. The exhaust from partial and full oxy-fuel cement plant configurations are coupled to the inlet of a C2CNT chamber in which CO2 is transformed by electrolysis in a molten carbonate electrolyte into CNTs at a steel cathode and pure oxygen at a nickel anode that is looped back in improving cement line energy efficiency and production rate. A partial oxy-fuel process looping O2 back through the plant calcinator has been compared to a full process in which it enters through the plant kiln. The first provides easier retrofit; the second maximizes efficiency by minimizing N2 throughput. Providing an economic impetus to carbon dioxide removal, per ton CO2 avoided the C2CNT cement plant consumes 50 electricity, emits no CO2, and produces 100 cement and ∼60, 000 of CNTs.